O mapa de ponta-cabeça - Costa, Maria Luiza Calim de Carvalho [UNESP] (My University, 2011)
Joaquin Torres Garcia reversed the position of the map of the continent, reaching South America north. This little drawing illustrates an article by Torres García, 1935, in which he advocates the creation of a "Escuela del Sur". This image illustrates a need in Latin America to seek their own ways. Torres-Garcia was inspired by the preColumbian American heritage for their symbolic and Constructivism proposes that Latin America look to the popular ancestral and cultural traditions and build an art itself through which the continent would no longer be a tributary of European culture. As production visual modern and contemporary Latin American context of globalization, takes the center / periphery relationship? The colonizer's model center/periphery relationship persists in the Latin American visual production? The technologies offered other ways of representation that break with the culture of repetition? These questions guide our research.
Keywords: Joaquin Torres Garcia; Latin American art